Study on numerical simulation method of viscosity time-varying slurry diffusion law - Zhang, Guohua; Zhang, Jiaxing; Pei, Xiangjun; He, Zhihao; Zheng, Guoxun (Frontiers in Earth Science, 2023)
In this study, finite element and finite difference methods were used for numerical calculations. The law of slurry diffusion in the inclined plane cracks is summarized in this study. Further, the equation describing the diffusion of slurry with time-varying viscosity in the plane fracture with dip angle was derived, and the mathematical model of slurry diffusion control equation and improved entropy clustering algorithm were developed. Thus, the law of slurry diffusion with time-varying viscosity in an inclined plane fractured rock mass was studied in detail, and the control equation obtained was modified to improve the prediction accuracy of diffusion of slurry with time-varying viscosity. By applying the model to actual working conditions, the results highlighted that the improved entropy clustering algorithm could more accurately describe the relationship between the factors influencing slurry diffusion and the slurry diffusion radius. The improved entropy clustering algorithm model can adjust the weights of the factors influencing the slurry diffusion in the diffusion control equation, which leads to a more flexible and more accurate slurry diffusion control equation.